Automated High-Throughput Flow Cytometry for High-Content Screening in Antibody Development. (August 2018) - Wang, Yana; Yoshihara, Tomoki; King, Samson; Le, Tinh; Leroy, Patrick; Zhao, Xiansi; Chan, Ching Kit; Yan, Zhong-Hua; Menon, Saurabh
The tedious sample preparation for flow cytometry limits the throughput and thus its usage as a primary screening method despite its sensitivity and accuracy. With the growing focus on utilizing antibodies as a therapeutic modality in drug discovery, it is critical to develop a high-throughput flow cytometry (HTFC) workflow to cope with the increasing need to support antibody discovery programs. We have developed a seamless HTFC sample preparation and readout workflow using the HighRes modular robotic system and the IntelliCyt iQue Screener PLUS. To fully utilize the advantages offered by flow cytometry, we typically multiplex multiple cell lines of interest in one well to simultaneously quantitate on-target activity and nonspecific activity along with measurement of antibody concentration. The ability to measure multiple parameters coupled with speed and increased accuracy provides gains in productivity and helps speed up antibody lead discovery.